2017
DOI: 10.1111/ctr.12942
|View full text |Cite
|
Sign up to set email alerts
|

The high incidence of severe chronic kidney disease after intestinal transplantation and its impact on patient and graft survival

Abstract: The incidence of CKD after ITx is extremely high and its development drastically limits post-transplant survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…There is high incidence of kidney failure in CIF and ITx patients and in the latter is an independent risk factor for poor outcome. 36 Therefore, we have a low threshold to a add a kidney graft in case of significantnot yet terminalpretransplant kidney dysfunction. In our…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…There is high incidence of kidney failure in CIF and ITx patients and in the latter is an independent risk factor for poor outcome. 36 Therefore, we have a low threshold to a add a kidney graft in case of significantnot yet terminalpretransplant kidney dysfunction. In our…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…One of the major challenges following IT is the significant decline in renal function with associated morbidity and mortality 6,7 . Patients considered for IT or MVT undergo a comprehensive assessment including determination of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of CKD in IT is variable with a 5‐year cumulative incidence of 21.3% published in 2003 6 . More recently, Huard et al 7 reported a cumulative incidence of 3.2%, 25.1%, and 54.1% at 1, 5, and 10 years after IT. This was associated with a sixfold increase in mortality.…”
Section: Introductionmentioning
confidence: 99%
“…About 18.1% of cases had a GFR <30 mL/min, 7.4% required initiation of chronic hemodialysis, while 4.4% needed a subsequent kidney transplant. Development of severe CKD was an independent risk factor for mortality with hazard ratio of 6.2 …”
Section: Discussionmentioning
confidence: 99%